The Power of Influence: Examining the Impact of YouTube Ads on Purchase Intention through Brand Awareness among Indonesian Audiences - Mohamad Trio Febriyantoro; Osrita Hapsara (Cita konsultindo, 2023)
This study aims to analyze whether Youtube Ads have an effect on Purchase Intention by using Brand Awareness as a mediating variable. Respondents in this study were audiences who had watched advertisements on Youtube Jakarta which were selected using the non-probability sampling method with the purposive sampling method. This research uses Patrial Least Square Structural Equation Modeling (PLS-SEM) with WarpPLS version 7.0. This study measures how Youtube Ads influence Brand Awareness, Brand Awareness influences Purchase Intention and Youtube Ads is directly related to Purchase Intention. The results show that Entertainment has a significant effect on Brand Awareness, Informativeness has a significant effect on Brand Awareness Irritation has no significant effect on Brand Awareness, Customization has a significant effect on Brand Awareness, Brand Awareness has a significant effect on Purchase Intention and Brand Awareness cannot act as a mediating relationship between YouTube Ads and Purchase Intention.